Chronique juridique - Létourneau, Alain; Moreau, Rémi (Assurances, 1983)
Once again, lawyers Alain Létourneau and Rémi Moreau provide contributions; the former discusses the condition of average referred to in article 2488 of the Civil Code, while the latter comments on the settlement of automobile claims. On the condition of average, Me Létourneau looks at an important legal decision which takes into account traditional iegal ideas as well as new tendencies. Regarding automobile insurance claims settlement, Me Moreau briefly describes the contractual application of the Quebec automobile insurance policy.